Interannual fluctuations in the seasonal cycle of nitrous oxide and chlorofluorocarbons due to the Brewer‐Dobson circulation. Issue 19 (1st October 2013) - Simmonds, P. G.; Manning, A. J.; Athanassiadou, M.; Scaife, A. A.; Derwent, R. G.; O'Doherty, S.; Harth, C. M.; Weiss, R. F.; Dutton, G. S.; Hall, B. D.; Sweeney, C.; Elkins, J. W.
<x xml:space="preserve">Abstract</x> [1] The tropospheric seasonal cycles of N2O, CFC‐11 (CCl3F), and CFC‐12 (CCl2F2) are influenced by atmospheric dynamics. The interannually varying summertime minima in mole fractions of these trace gases have been attributed to interannual variations in mixing of stratospheric air (depleted in CFCs and N2O) with tropospheric air with a few months lag. The amount of wave activity that drives the stratospheric circulation and influences the winter stratospheric jet and subsequent mass transport across the tropopause appears to be the primary cause of this interannual variability. We relate the observed seasonal minima of species at three Northern Hemisphere sites (Mace Head, Ireland; Trinidad Head, U.S.; and Barrow, Alaska) with the behavior of the winter stratospheric jet. As a result, a good correlation is obtained between zonal winds in winter at 10 hPa, 58°N–68°N, and the detrended seasonal minima in the stratosphere‐influenced tracers. For these three tracers, individual Pearson correlation coefficients (r) between 0.51 and 0.71 were found, with overall correlations of between 0.67 and 0.77 when "composite species" were considered. Finally, we note that the long‐term observations of CFCs and N2O in the troposphere provide an independent monitoring method complementary to satellite data. Furthermore, they could provide a useful observational measure of the strength of stratosphere‐troposphere exchange and, thus, could be used to monitor any long‐term trend in the Brewer‐Dobson circulation which is predicted by climate models to increase over the coming decades.